Produção de vetores recombinantes para expressão de diferentes formas da proteína K1 do herpesvírus associado ao Sarcoma de Kaposi (KSHV) - Silvestre,Renata Nacasaki [UNESP] (2012)
Kaposi´s sarcoma associated herpesvirus (KSHV) or human herpesvirus 8 (HHV-8) is a gammaherpesvirus essential for the development of all forms of Kaposi´s sarcoma (KS). The KSHV’s life cycle is basically divided into latent and lytic phases, which have distinct viral gene expression profiles. Some important oncogenic products of KSHV are expressed during the lytic phase, including the viral K1 protein. As an effect of interfer-ence with intracellular signaling, K1 expression increases proliferation and survival of KSHV-infected cells. Due to its high level of genetic variability compared to other re-gions of the viral genome, the K1-encoding ORF (ORF-K1) is commonly evaluated for KSHV genotyping. It remains unclear whether different viral genotypes have particular biological effects that might modify the KSHV oncogenicity. The present study aimed to contribute to the establishment of an experimental in vitro model for evaluation of the K1 protein from common KSHV genotypes. Recombinant expression vectors with the ORF-K1 from KSHV genotypes A, B and C were prepared by genetic cloning. The recombi-nant vectors pKSHVOK1 obtained by cloning were sequenced for structural validation. After that, HEK293 cell line was transfected with the recombinant vectors, and proteins were extracted for expression analysis by Western blot technique, for K1 functional vali-dation. Results showed that ORF-K1 vectors containing KSHV ORF-K1 from the A, B and C genotypes were produced and structurally validated by DNA sequencing. The K1 expression at the protein level was also confirmed by immunoblots using an antibody for FLAG detection, an epitope from the vector that binds to K1. Based on presented re-sults, it´s possible to conclude that the recombinant vectors will be able to be used in future studies of K1 protein biological properties from distinct KSHV genotypes